2015
DOI: 10.1111/sms.12531
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity among adolescents: The role of various kinds of parental support

Abstract: The objectives of this study were (a) to examine the association between various kinds of parental social support and adolescents' physical activity (PA) and (b) to examine whether various kinds of social support from mothers and fathers were differently associated with boys' and girls' PA. Data came from the Aarhus School Survey that included 2100 schoolchildren at 11, 13, and 15 years of age. Parental social support for PA was measured by items about encouragement to do PA, doing joint PA, parents watching P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 35 publications
2
15
1
6
Order By: Relevance
“…Emotional support from parents was negatively associated with MVPA and LPA in the full models, and follow-up analysis demonstrated that this effect was more strongly shown for adolescent males. This is in contrast to several previous studies that found positive associations [33,55,75,[98][99][100] or no association [32,101] between PA and emotional support. However, previous investigators who examined the relationship between emotional support and PA in predominantly African American sample have found positive associations for LPA, but no relationship between emotional support and MVPA [56].…”
Section: Discussioncontrasting
confidence: 99%
“…Emotional support from parents was negatively associated with MVPA and LPA in the full models, and follow-up analysis demonstrated that this effect was more strongly shown for adolescent males. This is in contrast to several previous studies that found positive associations [33,55,75,[98][99][100] or no association [32,101] between PA and emotional support. However, previous investigators who examined the relationship between emotional support and PA in predominantly African American sample have found positive associations for LPA, but no relationship between emotional support and MVPA [56].…”
Section: Discussioncontrasting
confidence: 99%
“…In certain conservative cultures, however, parental, especially mother's education has been found to have an influence on girls' PA [35]. A study conducted in Denmark found that while adolescent girls received significantly higher level of encouragement from their mothers, a higher proportion of boys than girls reported fathers watched them when they were physically active [12]. This suggests that there may be different dimensions of parental support in adolescents' PA, which deserve further investigation particularly in a diverse cultural context.…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining gender differences in parental support have yielded mixed results. While a number of studies have reported no significant differences in the influence of fathers or mothers on their children's PA [11,12], there is evidence to suggest that parents may provide greater support for PA to boys compared to girls [13,14]. However, little is known about the interactions between parental support and environmental factors (e.g., safety, access to PA facilities) or cultural factors (e.g., ethnicity, social class, gender expectation) which may influence children's PA.…”
Section: Introductionmentioning
confidence: 98%
“…29 In addition, data from the Aarhus School Survey, including 2100 children at 11, 13, and 15 years of age, examined the importance of families and peers for children's sports participation. 30,31 Overall, the identified data indicated a close relationship between parents and their children's participation in sports: if both parents take part in sport, 91% of their children also participate in sport. If none of the parents practices sport, 79% of the children participate in sport.…”
Section: Family and Peers: Incmentioning
confidence: 99%